RELAÇÕES ENTRE CONSUMO PRÉVIO DE CARBOIDRATO SOBRE A GLICEMIA CAPILAR DE PRATICANTES DE MUSCULAÇÃO DURANTE UMA SESSÃO DE TREINO RESISTIDO - Breno da Silva Lozi; Pedro Augusto de Carvalho Mira; Denise Félix Quintão (Universidade do Estado do Rio de Janeiro, 2018)
The aim of the current study is to evaluate the relation between previous carbohydrate intake and blood glucose behavior in bodybuilders during  resistance training sessions. A randomized placebo-controlled study was conducted with 15 participants selected for the experimental group and with 15 ones for the placebo group (29±5 vs. 28±7 years, respectively, p=0.696), who presented physical fitness ranging from acceptable to excellent and were subjected to 10-hour fasting before the training session. The experimental group ingested 250ml of a beverage containing 1g of simple carbohydrate (maltodextrin) per kg of body weight, whereas the placebo group ingested 250 ml of Clight® juice. Capillary glycemia was measured before and after drinking. Subsequently, glycemia was measured every 15 minutes during the training session and after 15-minute recovery. Two-way ANOVA, followed by Tukey post hoc test, was used to analyze the primary outcome. Significance level was set at p ≤ 0.05. The pre-session ingestion of the beverage containing 1g carbohydrate / kg of body weight caused: 1) hyperglycemic state 15 minutes after the ingestion (134.53 mg/dL ± 21.02); and 2) maintenance of capillary glycemia at adequate values for 15 min: 118.33; 30 min: 106.60; 45 min: 109.33; and 60 min: 105.27 mg/dL; and at recovery 103.67 mg/dL; however, these values were higher than the ones recorded for the placebo group (pre-session: 85.33; 15 min: 85.40; 30 min: 87.27; 45 min: 90.47; 60 min: 90.60; 15 min recovery: 88.73 mg/dL). Previous carbohydrate intake significantly increased glycemia in the control group, whereas no hypoglycemia was observed in the placebo group. There is no need for individuals to be subjected to supplementation with carbohydrate beverages prior to the training session in order to prevent hypoglycemia. DOI: 10.12957/demetra.2018.31022